EVALUASI PROGRAM DIKLATPIM IV PADA BALAI DIKLAT KEAGAMAAN MAKASSAR DENGAN MODEL KIRKPATRICK - FIRMAN BASIR (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2013)
This research aimed to know the effectiveness of the education and training leadership IV at Makassar Education and Training Religious Center using the four-level evaluation of Kirkpatrick Models, namely: reaction, learning, behavior, and result. The evaluation results on reaction level which have not satisfied the participants were the mastery of the materials and the ability of the trainers to use case samples according to participants’ duties and functions, the relevance of materials to participants’ duties and functions, assigned tasks, dorm comforts, learning facilities, sports and recreation center, food service and hospitality, as well as the appearance of the waiter in the dining room. There was an improvement of learning outcomes on the evaluation results on learning level. The less satisfactory evaluation results on behavior level was the ability of the education and training alumni to develop a solid working team and making decisions. On the result level was the quality of service of educnation and training alumni. To improve the service quality of the education and training leadership IV, the Makassar Religious Training Center should manage the findings which were less satisfactory on every aspect mentioned above.